Carl Nielsen under the Influence. Some New Sources for the First Symphony - Fanning, David (Carl Nielsen Studies, 2008)
Nielsen’s general musical affinities are often mentioned, and in some cases they are well documented. But even in a work as characterful and characteristic as the First Symphony, there are several prima facie cases of allusion to specific works – from Berlioz to Lange-Müller – that have not previously been identified. The point of proposing and discussing them here is not to downgrade the originality of Nielsen’s symphonic breakthrough piece, but rather to lead towards a closer understanding of what makes it unique, by showing how it borrows ideas only to go beyond them and to reveal new potential.